Acute Pancreatitis in the Course of Meprobamate Poisoning - Fathallah, Neila; Zamy, Michele; Slim, Raoudha; Fain, Olivier; Hmouda, Houssem; Bouraoui, Kamel; Salem, Chaker Ben; Biour, Michel (JOP. Journal of the Pancreas, 2011)
Context We report a case of massive poisoning with meprobamate leading to acute pancreatitis. Case report A 43-year-old patient with a history of schizophrenia and multiple suicide attempts was admitted to the intensive care unit for severe poisoning with meprobamate (voluntary ingestion of 60 g). On admission, the patient was deeply comatose with low blood pressure and hypothermia. Laboratory analysis revealed leukocytosis and high lipase and amylase serum levels. There was no eosinophilia. Abdominal computed tomography showed pancreatitis grade A. The patient was intubated and ventilated, and intravenous dopamine was infused. The patient regained consciousness and was extubated five days later. Improvement in pancreatic tests was noted several days later. The outcome was favorable. Discussion According to the Naranjo probability scale, meprobamate-induced acute pancreatitis was probable. Acute pancreatitis in meprobamate poisoning is exceptional. The pathogenesis of pancreatitis-induced meprobamate poisoning may be explained by two mechanisms: stimulation of pancreatic secretion secondary to cholinergic activation and pancreatic ductal hypertension. Conclusions The signs of severe meprobamate toxicity are numerous including cardiovascular and central nervous symptoms. Acute pancreatitis should also be added as a possible manifestation of meprobamate poisoning. Image: Faculty of Medicine of Sousse. Sousse, Tunisia.